Studi Manajemen Waktu Proyek Pembangunan Rumah Sakit Islam Malang - Lalisuk, Stefanus; Suhudi ; Wijaya,, Handika Setya (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Construction Management is one of the most important sciences and needs to be mastered in carrying out a project. One part of project management itself is time management. The time management system is one of the determinants of the success of the contractor in managing the project, especially in terms of time. Appropriate job schedule settings can minimize the obstacles that may occur in the implementation of the project. In each scheduling must pay attention to the order of each job so that a separate experience is needed for the planner. One important part of time management itself is the measurement of work performance. This is done so that the implementer can find out how much work weight has been completed based on Time Schedule. Earned Value Method Being one of the options as an indicator in measuring the progress of work carried out in Malang Islamic Hospital Building. The use of Earned Value can be seen from the progress of the work project implemented and can predict the completion time of the Malang Islamic University hospital construction project.